2021
DOI: 10.3389/fphar.2021.800522
|View full text |Cite
|
Sign up to set email alerts
|

Shenkang Injection and Its Three Anthraquinones Ameliorates Renal Fibrosis by Simultaneous Targeting IƙB/NF-ƙB and Keap1/Nrf2 Signaling Pathways

Abstract: Oxidative stress and inflammation are important and critical mediators in the development and progression of chronic kidney disease (CKD) and its complications. Shenkang injection (SKI) has been widely used to treat patients with CKD. Although the anti-oxidative and anti-inflammatory activity was involved in SKI against CKD, its bioactive components and underlying mechanism remain enigmatic. A rat model of adenine-induced chronic renal failure (CRF) is associated with, and largely driven by, oxidative stress a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 48 publications
(23 citation statements)
references
References 88 publications
0
22
0
Order By: Relevance
“…Previous research has shown that Shenkang injection can negatively regulate TGF-/Smads signaling by lowering TGF- and P-smad3 expression in 5/6 nephrectomized rats, thereby delaying the progression of renal fibrosis and EMT of renal tubular epithelial cells ( Wu et al, 2015 ). Luo et al (2021) showed that SKI and its components (including chrysophenol, emoflavin, and emoflavic acid) can target the IƙB/NF-ƙB and Keap1/Nrf2 ( Chen et al, 2019 ) signaling pathways to inhibit oxidative stress and inflammation, thereby preventing renal fibrosis. The Janus kinase/signal transduction and transcriptional activator (JAK/STAT) pathway is a multipotent signal cascade of multiple growth factors and cytokines, and activation of the JAK/STAT pathway is increased in renal interstitial fibroblasts induced by unilateral ureteral obstruction (UUO) ( Darnell et al, 1994 ).…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has shown that Shenkang injection can negatively regulate TGF-/Smads signaling by lowering TGF- and P-smad3 expression in 5/6 nephrectomized rats, thereby delaying the progression of renal fibrosis and EMT of renal tubular epithelial cells ( Wu et al, 2015 ). Luo et al (2021) showed that SKI and its components (including chrysophenol, emoflavin, and emoflavic acid) can target the IƙB/NF-ƙB and Keap1/Nrf2 ( Chen et al, 2019 ) signaling pathways to inhibit oxidative stress and inflammation, thereby preventing renal fibrosis. The Janus kinase/signal transduction and transcriptional activator (JAK/STAT) pathway is a multipotent signal cascade of multiple growth factors and cytokines, and activation of the JAK/STAT pathway is increased in renal interstitial fibroblasts induced by unilateral ureteral obstruction (UUO) ( Darnell et al, 1994 ).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the studies of TCMs have attracted attention owing to its superiority in the treatment of refractory diseases ( Chen et al, 2016b ; Li et al, 2021a ; Shao G. et al, 2021 ; Wang Y. W. et al, 2021 ; Yang and Wu, 2021 ). A variety of compounds isolated from natural products have been protected against renal fibrosis ( Feng et al, 2019b ; Luo et al, 2021 ; Shao M. et al, 2021 ; Zhao et al, 2011 ; Zhou F. et al, 2021 ). Therefore, natural products have attracted more and more attention around the world and are committed to the development of new drugs.…”
Section: Natural Products As An Alternative Therapy Against Tubuloint...mentioning
confidence: 99%
“…Intriguingly, natural products are one of the most promising therapies for a broad spectrum of refractory diseases including coronavirus disease 2019 and its complications ( Chen et al, 2018a ; Chen et al, 2018b ; Izzo et al, 2020 ; Yang et al, 2021a ; Yang et al, 2021b ; Zhang et al, 2021b ; Singla et al, 2021 ; Zuo et al, 2021 ). Mounting natural products have been demonstrated to exhibit excellent efficacy for CKD treatment ( Wang et al, 2018b ; Zhang et al, 2020c ; Geng et al, 2020 ; Meng et al, 2020 ; Miao et al, 2020 ; Lan, 2021 ; Li et al, 2021 ; Luo et al, 2021 ; Miao et al, 2022 ; Yu et al, 2022 ). Although a number of natural products could mitigate MN, the natural products in MN application are still in its infancy compared with CKD.…”
Section: Treatment Of Membranous Nephropathymentioning
confidence: 99%